2000
DOI: 10.1007/s001670000134
|View full text |Cite
|
Sign up to set email alerts
|

Type V collagen is increased during rabbit medial collateral ligament healing

Abstract: To understand the reparative process of medial collateral ligament (MCL), fibrillar collagen and their relative ratios in healing MCL with anterior cruciate ligament (ACL) reconstruction were analyzed. Skeletally mature New Zealand white rabbits were subjected to a mop-end tear of MCL without repair with ACL reconstruction. Rabbits were killed 6 and 52 weeks after injury. Ligamentous tissues from the injury site and sham controls were soaked in 0.5 M acetic acid for 24 h, minced, and treated with pepsin to sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 22 publications
1
74
0
2
Order By: Relevance
“…Contrary to the findings of Dressler et al (2002), in the present study, type V collagen was readily detectable in tendons of young rats and mRNA expression was decreased in old rats, although the decrease was less pronounced than the decrease of type I collagen mRNA expression in tendons of old rats. In a separate study, increased expression of type V collagen correlated with accumulation of the smaller diameter collagen fibrils after ligament injury (Niyibizi et al 2000), and a study by Lu et al (2011) showed that collagen type V expression was increased in injured tendons. Thus, understanding of the role of type V collagen in tendon and ligament function and its role in aging and injured tendons warrants further evaluation.…”
Section: Discussionmentioning
confidence: 91%
“…Contrary to the findings of Dressler et al (2002), in the present study, type V collagen was readily detectable in tendons of young rats and mRNA expression was decreased in old rats, although the decrease was less pronounced than the decrease of type I collagen mRNA expression in tendons of old rats. In a separate study, increased expression of type V collagen correlated with accumulation of the smaller diameter collagen fibrils after ligament injury (Niyibizi et al 2000), and a study by Lu et al (2011) showed that collagen type V expression was increased in injured tendons. Thus, understanding of the role of type V collagen in tendon and ligament function and its role in aging and injured tendons warrants further evaluation.…”
Section: Discussionmentioning
confidence: 91%
“…After protein extraction, the salt insoluble tissue pellets were used to determine the ratio of collagen subtypes III/I 11,12 . Following pepsin digestion, samples were isolated on 6% gels by interrupted sodium-dodecyl sulfate gel electrophoresis (SDS-PAGE).…”
Section: Interrupted Sds-page For Collagen Subtypesmentioning
confidence: 99%
“…Some of the molecules such as collagen type V and decorin have been implicated in collagen fibrillogenesis. 2,[16][17][18] Electron microscopic analysis of ligaments has shown a bimodal distribution of collagen fibril diameters in normal rabbit medial collateral ligaments. 19 Histologically, collagen in ligament and tendon displays a crimp pattern, which refers to a regular, wavy pattern of the matrix when viewed in unloaded conditions.…”
Section: Properties Of Ligaments and Tendonsmentioning
confidence: 99%